The Role of the Kelompok Kerja Guru (KKG) in Implementing Lesson Study to Improve the Performance of Elementary School Teachers - Suwarno, Suwarno; Riyanto, Yatim; Wuryani, Eni (International Journal for Educational and Vocational Studies, 2020)
Law of the Republic of Indonesia Number 14 of 2005 concerning Teachers and Lecturers article 20 paragraph (b) mandates that to carry out their professional duties, teachers are obliged to continuously improve and develop academic qualifications and competencies in accordance with the development of science, technology, and art (Undangundang Republik Indonesia Nomor 14 Tahun 2005). The existence of this law is expected to provide the right opportunity to improve its professionalism through training, writing scientific papers, Kelompok Kerja Guru (KKG) and Musyawarah Guru Mata Pelajaran (MGMP). This research uses a qualitative approach. The informants used in this study were the teachers who were members of the Kelompok Kerja Guru Cluster 2, Duduksampeyan Regency, Gresik Regency who implemented the 2013 curriculum. The technique of taking research informants conducted in this study was using non probability sampling. Non-probability sampling techniques used in this study were purposive sampling and snowball sampling. Kelompok Kerja Guru are also forums or places that can be used to foster and enhance the professionalism of elementary school teachers (Depdiknas, 1997: 46). KKG has benefits including as a place to accommodate and solve problems faced by teachers in teaching and learning activities, discussions, examples of teaching, demonstration of the use and manufacture of teaching aids (Alwi, 2009). Based on the discussion of research findings about the role of the Teacher Working Group (KKG) in implementing learning to improve the performance of elementary school teachers, there can be some conclusions that the role of the Kelompok Kerja Guru in carrying out the stages of lesson study activities has been effective because the KKG can provide understanding, guidance, goals, and benefits of lesson study.